2017
DOI: 10.1080/07420528.2017.1407778
|View full text |Cite
|
Sign up to set email alerts
|

Eveningness is associated with skipping breakfast and poor nutritional intake in Brazilian undergraduate students

Abstract: Some studies have proposed that self-reported eveningness, which reflects the preference of performing activities in the evening, may harm nutritional health and influence the eating behavior and nutritional status of individuals. However, the relationship between these variables (eveningness and nutritional status) and the consumption of breakfast, which is currently considered a marker of health, has been insufficiently explored by studies. The aim of this study was to investigate, in undergraduate students,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 42 publications
3
47
0
3
Order By: Relevance
“…In addition, daily routines could also mediate the association between skipping breakfast and an increased risk of depressive symptoms. Previous studies have shown that individuals with the skipping-breakfast habit also have other health-related behaviors, including internet addiction [35], a lower physical activity level [53], and evening-type preferences [54]. Interestingly, internet addiction [55], lower physical activity level [56], and evening-type preferences [57] have been suggested to increase the risk of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, daily routines could also mediate the association between skipping breakfast and an increased risk of depressive symptoms. Previous studies have shown that individuals with the skipping-breakfast habit also have other health-related behaviors, including internet addiction [35], a lower physical activity level [53], and evening-type preferences [54]. Interestingly, internet addiction [55], lower physical activity level [56], and evening-type preferences [57] have been suggested to increase the risk of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also revealed an association between skipping meals and chronotype. Many previous studies have reported an association between skipping breakfast and evening type (27,44,45). Skipping breakfast is unhealthy eating behavior which contributes to metabolic disorders including obesity and diabetes (46,47).…”
Section: Discussionmentioning
confidence: 98%
“…The results of the present study suggest that evening cronotype can be one of the factors which can lead to excessive pregnancy weight gain. In non-pregnant women, a higher weight and BMI have been associated with as worse healthier indicators in evening people (Anothaisintawee et al, 2018) such as metabolic syndrome (Yu et al, 2015) and more risk to heart diseases (Yu et al, 2015), as well as worse feeding behavior (Teixeira et al, 2018). These data could contribute to explain the association between weight gain during early pregnant period and chronotype of these women in our study.…”
Section: Discussionmentioning
confidence: 50%
“…Pesquisas realizadas nos últimos anos no âmbito da saúde e nutrição vêm sinalizando a participação dos ritmos biológicos na sincronização do comportamento alimentar de seres humanos (GOLOMBEK & ROSENSTEIN, 2010). Nessa linha, a associação entre o cronotipo e o comportamento alimentar tem sido abordado em alguns estudos (ROßBACH et al, 2017;PATTERSON et al, 2016;, que mostram que a vespertinidade parece influenciar negativamente os hábitos alimentares (MOTA et al, 2016;SILVA et al, 2016) e o estado nutricional (TEIXEIRA et al, 2018), associando-se ao maior consumo de alimentos doces, alimentos ricos em colesterol (MOTA et al, 2016) e maior quantidade de calorias no período da noite (MUÑOZ et al, 2016).…”
Section: Introductionunclassified
See 1 more Smart Citation